Potential market overlap between the Gautrain and the PRASA modernisation program - Laabmayr, Elzane (Department of Civil Engineering, 2020)
The Gauteng Province is the only province in South Africa with two rail services, namely Metrorail, operated through the Passenger Rail Agency of South Africa (PRASA), and Rapid Rail, known as the Gautrain, operated by the Gautrain Management Agency (GMA). It is widely known that these rail services do not compete for passengers as they currently serve different markets. Based on passenger survey data, PRASA currently serves the Low and Middle Income markets while the Rapid Rail serves the Upper Middle and High Income markets. PRASA has published their modernisation plans, with a focus on upgrading the Gauteng Metrorail network in the future. It is currently unclear whether these upgrades could result in a rail market overlap between Rapid Rail services and the PRASA Modernisation services. The rail market overlap holds two scenarios, a complimentary overlap and a competitive overlap. A complimentary overlap involves one rail service integrating with another, resulting in a potential increase in patronage for both services. Such an overlap is aligned with the Gauteng 25-Year Integrated Transport Master Plan (GITMP25) vision, whereby the Gauteng public transport system is integrated across multiple modes and services and would thus promote the use of the public transport system. For this overlap to take place, the rail services should serve similar markets, different geographical nodes and integrate at key transfer nodes while not competing for passengers along corridors. A competitive overlap is one where two rail services serve similar, if not the same, markets and nodes and compete for passengers along the transport corridors. Such an overlap does not support the vision of the GITMP25 as a competitive overlap requires fully operational infrastructure for both services, only to divide existing public transport users between the two services. This form of overlap is not sustainable and does not attract new public transport users to the services. In order to investigate whether the Rapid Rail and PRASA Modernisation services will have a competitive overlap, it is necessary to understand the existing and potential future rail operators’ markets, passengers’ travel behaviour and evaluate the services’ geographical overlap. Once the overlap is identified and quantified, the results will be able to guide future transport planning to minimise competitive overlap in rail services and focus on complimentary overlap to help build an integrated public transport system for the Gauteng Province. To demonstrate this, this study evaluated the existing rail services in the Gauteng Province and defined the respective sociodemographic market segmentation and mode choice drivers. A hypothetical rail market was developed for the proposed PRASA Modernisation service, aligning with the proposed service’s upgrade plans. A Multi-criteria Analysis (MCA) tool was developed to align the Rapid Rail, existing Metrorail and proposed PRASA Modernisation rail services with their respective markets in terms of income brackets. Thereafter, MCA was used to determine the overlap in markets between the three rail services. The MCA identified that the PRASA Modernisation service would expand the Metrorail market into the Upper Middle Income category as a result of the service’s expected improvements. The PRASA Modernisation Upper Middle Income market was therefore identified as the potential overlapping market with the current Rapid Rail service. The potential competitive market overlap between the Rapid Rail and PRASA Modernisation rail services were evaluated in terms of geographical market overlap, trip pattern overlap and trip making overlap. The ultimate overlap between the Rapid Rail and the PRASA Modernisation services resulted in 12% of the overall Rapid Rail patronage. Finally, an estimated uptake of the overlapping market was developed using the quantitative mode choice drivers, namely travel time and travel cost. The weightings of these mode choice drivers were aligned with that of the Rapid Rail market and the travel time and travel cost of each rail service was normalised over an average trip distance between Pretoria and Johannesburg CBDs. The estimated service uptake resulted in 58% of the overlapping market remaining to use the Rapid Rail service and 42% of the overlapping market shifting to use the PRASA Modernisation service. However, the Rapid Rail park-and-ride facilities are used by more than 40% of the Rapid Rail passengers. Without this infrastructure at the PRASA Modernisation stations, the potential uptake of the PRASA Modernisation service from existing Rapid Rail services could be diminished from 41% to 25% due to the lack of an integrated Metrorail system with private cars. The final competitive overlapping market between the Rapid Rail and PRASA Modernisation services resulted in 3 – 5% of the total Rapid Rail patronage. The research study concludes that the competitive overlap between the Rapid Rail and PRASA Modernisation services would be negligible as these services will continue to serve different markets. It is therefore recommended for the PRASA Modernisation program to be implemented to assist in the much needed rejuvenation of the Gauteng Metrorail service. It was further recommended that the PRASA Modernisation program incorporates integrated feeder and distributor services, strengthening the attractiveness of the PRASA Modernisation service and aiding in the GITMP25’s vision of developing an integrated and efficient transport system in Gauteng.